Application of TIO2 nanostructure using hydrothermal method for waste water treatment - Chin, Soon; Ahmad, Mohd Khairul; Mohd Fazli, Fatin Izyani; Abd Hamed, Noor Kamalia; Hamidi, Indah Fitriani; Khalid, Noor Sakinah (Asian Research Publishing Network (ARPN), 2015)
"Titanium dioxide (TiO2) can be used as a photo-degradation material. TiO2 nanostructured has been successfully fabricated by hydrothermal method. The objective of this study is to optimize the TiO2 nanostructures for waste water treatment. Titania Degusa P25 and sodium hydroxide (NaOH) were treated hydrothermally with different concentrations of NaOH i.e. 1, 5 and 10 M. The morphology of the samples were characterized using FESEM and XRD for structural analysis. All the samples were observed to have clumps of nanowires based on the FESEM images. XRD analysis showed that the samples produced were anatase phase. Later, the TiO2 nanostructures were applied to waste water treatment. "